Effect of Thermo-mechanically Fermented Soybean Meal on Nutrient Digestibility and Carboxymethyl Cellulase Activity of Jawa Super Chicken - Yano, Aan Andri; Suprayogi, Wara Pratitis Sabar; Darmawan, Muhammad Arif; Saputro, Wahyu Subagio; Saraswati, Pramita Nindya; Setyono, Wahyu; Akhirini, Novi (Faculty of Animal Science, Universitas Brawijaya, 2024)
In poultry, amino acids are sourced mainly from soybean meal (SBM). However, nutrient absorption and digestion are quickly reduced in the presence of antinutritional factors (ANFs), thus impairing poultry growth performance. Here, we experimented to determine the effects of fermented SBM with A. niger and B. subtilis on nutrient digestibility and carboxymethyl cellulase (CMCase) activity of Jawa Super (Joper) chicken. The experiment was completed from November 2022 to January 2023 on the poultry farm of the Animal Science Faculty, Universitas Sebelas Maret Surakarta, Indonesia. A total of 36 1-d-old Joper male chicks were randomly allocated into three dietary treatments; Control diet without fermented SBM (CON), fermented SBM with B. subtilis (P1), and fermented SBM with A. niger (P2) in a completely randomized design. The nutrient digestibility and CMCase activities were analyzed in response to a modified feeding using fermented SBM. Analysis of variance (ANOVA) was employed to analyze data using SPSS® Statistics 25 for Windows. There was a significant difference in the digestibility of crude protein (CP), dry matter (DM), crude fat, nitrogen-free extract (NFE), and organic matter (OM) between the control and treatment groups (P < 0.05). However, crude ash and fibre digestibilities are relatively similar (P > 0.05). Following the insignificant result of fiber digestibility, CMCase activities did not differ significantly (P > 0.05). To conclude, feeding Joper chicken with fermented SBM seems promising in achieving optimized digestibility of nutrients due to significant results, especially in CP digestibility. Additionally, within the treatment groups, B. subtilis (P1) demonstrated slightly better performance compared to A. niger (P2).